A study on evaluation of ASHAs for their knowledge, attitude and practice towards newborn care in Howrah district of West Bengal - Pattnayak, Ujjwal; Ray, Samir Kumar; Madhwani, Kishore P.; Singh, Jitendra Kumar (International Journal of Research in Medical Sciences, 2019)
Background: : Accredited Social Health Activist (ASHA) is a trained female community health activist. ASHAs are local women trained to act as facilitator and promoters of health care in their communities. ASHA is trained to work as an interface between the community and the public health system. ASHA play an important role in newborn care to reduce their morbidity and mortality. Methods: Data were collected from ASHAs working in Shibbur area of Howrah District, west Bengal. The study sample consisted of 70 ASHAs working in the Shibpur area that fulfilled the inclusion criteria. A predesigned pretested questionnaire of ASHA was used to collect data in the study. Results: The mean age of ASHAs was 35.74 years. Only 32 (45.71%) had received middle level (class VIII) education. Only 45.71 % of ASHAs had good knowledge and practice regarding hypothermia and its complication and the procedure of providing warmth the baby after delivery. Only 57.1% of ASHA had good knowledge regarding counseling and problem solving on breast feeding. Only 38.57% had good knowledge and practices on identification and basic skill on management of Low Birth Weight (LBW) having birth weight of <2.5kg and pre-term baby (<37 weeks of gestation). Conclusions: In the present study, we found that Knowledge, Attitude and Practice of ASHAs were inadequate in some aspects of newborn care. This gap of knowledge should be taken seriously during training procedures so that effective knowledge and essential skill for newborn care can be imparted. During recruitment of ASHAs higher literally status should be given preferences.